Persepsi dan minat pemuda terhadap agribisnis sapi Madura (Studi di Kecamatan Waru, Kabupaten Pamekasan) - Ghirah Rizqy Daniar; Bambang Ali Nugroho; Eko Nugroho (Jurnal Ilmu-Ilmu Peternakan (Indonesian Journal of Animal Science), 2014)
The study was aimed to investigate the youth perception and interest on Madura cattle agribusiness. The respondents of this research were selected randomly from 100 youths aged 16-30 years. The method of the research was survey. The data were gathered from August to September 2014 in Waru sub district, Pamekasan regency. Primary data including perception, interests as well as internal and external factors were analyzed using descriptive analysis, chi square analysis  and rank spearman correlation analysis. Chi square analysis was used to determine the relationship between the internal and external factors of respondents to the interest on Madura cattle agribusiness. Spearman rank correlation analysis was used to determine the relationship between perception and interest of respondents on Madura cattle agribusiness. The results showed that youth had a good perception toward Madura cattle agribusiness because it was supported by conducive environment, had a high economic value, good support from the government and increased prestige. The highest interest on Madura cattle agribusiness was found based on a business plan creation. The internal factors (education level, gender, jobs and marital status) had a positive association with youth interest on livestock farming activities. Their interest was also positively related to external factors such as neighbor’s jobs and information searching activities.   Keywords: economic value, education, government support